Lockdowns in ASEAN : winning the pandemic war - Montesclaros, Jose Ma. Luis P. (2021)
With vaccines not expected to fully roll out until 2024, lockdowns remain a critical priority to save lives today. February 2021 marks the end of a year of COVID-19, and the opportunity to re-visit and improve the way lockdowns are implemented in the year ahead.